Analysis of Culinary Tourism and Local Product Uniqueness on Destination Image and Tourist Interest in Central Java - Apriyanto, Apriyanto; Susilo, Anton; Muhtadi, Muhamad Ammar (West Science Interdisciplinary Studies, 2025)
This study aims to analyze the uniqueness of culinary tourism and local products in shaping the destination image and influencing tourist interest in Central Java. The research adopts a quantitative approach with a sample of 150 respondents, using a Likert scale to measure the constructs, and employing Structural Equation Modeling with Partial Least Squares (SEM-PLS 3) for data analysis. The findings indicate that both culinary tourism and local product uniqueness significantly contribute to enhancing the destination image and increasing tourist interest. Culinary tourism positively affects destination image and tourist interest, while local product uniqueness has a stronger impact on destination image and tourist interest. The study emphasizes the importance of promoting Central Java's culinary heritage and local products as part of a comprehensive tourism strategy. The research provides valuable insights for tourism stakeholders seeking to strengthen the region's appeal through culinary tourism and cultural authenticity.